Preparation method of high-temperature-resistant polyacrylonitrile-based carbon fiber and application of high-temperature-resistant polyacrylonitrile-based carbon fiber in fireproof fabric

By adding specific accelerators to the carbon fiber preparation process and using technical means such as radiation heating preoxidation, the problems of high energy consumption, time-consuming, fiber unevenness and coalescence in the existing processes are solved, and the preparation of high-quality and high-performance high-temperature resistant polyacrylonitrile-based carbon fibers are achieved.

CN119615422AActive Publication Date: 2025-03-14ZHEJIANG TAIZHOU JINGZHEN TECH CO LTD +1

Patent Information

Application Number
CN202510155065.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-12
Publication Date
2025-03-14
Estimated Expiration
2045-02-12

AI Technical Summary

Technical Problem

In the existing carbon fiber preparation process, the pre-oxidation process consumes high energy and takes time, resulting in high manufacturing costs; at the same time, the high pre-oxidation temperature leads to excessive oxidation of the fiber surface layer and insufficient oxidation of the inner core, forming an uneven skin core structure, affecting the mechanical properties; in addition, the fibers are prone to coalescing, poor flexibility, and the fiber quality decreases after pre-oxidation at high temperatures.

Method used

A high-temperature resistant polyacrylonitrile-based carbon fiber is used to reduce the void index and coalescence rate of the fibrous filament by adding polyoxyethylene sorbitan monopalmitate, 2-acrylamino-2-methylpropanesulfonic acid and other accelerators; pre-oxidation is used to inhibit the formation of the skin core structure; hydrogen bromide gas is added during the pre-oxidation process to increase the oxidation rate; tar-like impurities on the surface of the fiber are removed by ultrasonic treatment; and finally carbonization is carried out in nitrogen.

Benefits of technology

The quality and performance of the fiber are improved and the manufacturing cost is reduced. By suppressing the formation of the leather core structure, the mechanical properties and flexibility of the fiber are improved. At the same time, the high temperature resistance and flame retardant properties of the fiber are improved.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a preparation method of high-temperature-resistant polyacrylonitrile-based carbon fiber and application of the high-temperature-resistant polyacrylonitrile-based carbon fiber in fireproof fabric. 2-acrylamido-2-methylpropanesulfonic acid is added, so that the limit oxygen index of the pre-oxidized fiber is increased, and the fireproof performance is enhanced; the coalescence rate of the pre-oxidized fibers is reduced by dipping perfluorolaurinol polyoxyethylene ether and spraying carbon powder; by spraying the basic aluminum chloride, the crimp number of the pre-oxidized fiber is increased, and the flexibility is improved; hydrogen bromide is added into oxygen, so that the oxidation rate and the limit oxygen index are improved; a pre-oxidation reaction is carried out in a radiation heating mode, and formation of a skin-core structure is inhibited; tar-shaped impurities deposited on the surfaces of the pre-oxidized fibers are removed under the action of ultrasonic waves, so that the quality of the carbon fibers is improved; the pre-oxidized fibers are treated through beta-anthraquinone sodium sulfonate, oxygen absorbed by the pre-oxidized fibers is removed, and the tensile strength of the carbon fibers is improved; therefore, the high-temperature-resistant and high-strength carbon fiber is prepared and is applied to a fireproof fabric.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of carbon fiber, and in particular to a method for preparing high-temperature resistant polyacrylonitrile-based carbon fiber and its application in fireproof fabrics. Background Art

[0002] Polyacrylonitrile-based carbon fiber and its composite materials have the characteristics of high strength and light weight. As structural materials, they are increasingly used in the fields of automobiles, sports, aviation, tools and military equipment. The preparation process of polyacrylonitrile-based carbon fiber mainly includes monomer polymerization, spinning curing, pre-oxidation, high-temperature carbonization and other processes.

[0003] Acrylonitrile-based polymers solidify from the surface to the inside during the spinning process. The surface layer of the fiber contacts the coagulation liquid and solidifies first; the inner core of the fiber solidifies at a slower rate. The surface layer that solidifies first further reduces the speed at which the coagulation bath diffuses into the inner core of the fiber, and also inhibits the coagulation bath from escaping from the fiber, resulting in a "skin-core" effect, causing the fiber to show uneven micron-level holes, reducing the fiber quality.

[0004] During the pre-oxidation process, the linear macromolecular chain undergoes cyclization, oxidation, dehydrogenation and other reactions to form insoluble and infusible fibers with a heat-resistant trapezoidal structure. This is a key link in the preparation of carbon fibers and has an important impact on the structure and properties of the final carbon fibers. The pre-oxidation process usually uses a furnace heating method to heat the spinning in hot air at 180°C to 400°C to achieve the purpose of pre-oxidation. However, the pre-oxidation process still has the following problems that need to be solved:

[0005] (1) The pre-oxidation reaction is usually carried out in a high-temperature oven or furnace at a temperature of 180°C to 400°C for 1 to 3 hours. It consumes a lot of energy and takes a long time, resulting in a high cost for carbon fiber manufacturing.

[0006] (2) During the pre-oxidation reaction, heat is transferred from the fiber surface to the fiber core, resulting in excessive oxidation of the fiber surface and insufficient oxidation of the fiber core, resulting in a skin-core structure with uneven pre-oxidation of the surface and core. The skin-core structure will be inherited by the subsequent carbonization treatment, increasing the structural defects of the carbon fiber and limiting the improvement of mechanical properties.

[0007] (3) Due to the high pre-oxidation temperature, the fibers are prone to agglomeration, resulting in poor quality of carbon fibers.

[0008] (4) When pre-oxidized at high temperature, the fiber becomes brittle and its flexibility decreases. When pre-oxidized and curled, it is easy to break and has poor spinnability.

[0009] (5) After the pre-oxidation reaction, tar-like impurities are deposited on the surface of the pre-oxidized fiber, affecting the quality of the carbon fiber.

[0010] Pre-oxidized fibers are carbonized at high temperatures to form carbon fibers. Due to the cumulative effects of many factors in process steps such as monomer polymerization, spinning solidification, pre-oxidation, and high-temperature carbonization, the quality of carbon fibers needs to be further improved to meet the high temperature resistance and high strength requirements of special industries. Summary of the invention

[0011] In order to solve the above problems, the first aspect of the present invention provides a method for preparing a high temperature resistant polyacrylonitrile-based carbon fiber, comprising the following steps:

[0012] Step S1, preparing spinning stock A: dissolving a polyacrylonitrile-based copolymer in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 20% to 30%, to prepare a spinning stock A;

[0013] Step S2, adding an accelerator: adding an accelerator 2-acrylamido-2-methylpropanesulfonic acid to the spinning stock A to prepare the spinning stock B;

[0014] Step S3, adding polyoxyethylene sorbitan monopalmitate: adding polyoxyethylene sorbitan monopalmitate to spinning stock B to prepare spinning stock C;

[0015] Step S4, preparing polyacrylonitrile fiber precursor: using a dimethylacetamide aqueous solution with a mass concentration of 40% to 50% as a coagulation bath, spinning the spinning stock C by wet spinning, pulling and stretching, and preparing polyacrylonitrile fiber precursor I;

[0016] Step S5, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the polyacrylonitrile fiber precursor I in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the polyacrylonitrile fiber precursor II;

[0017] Step S6, spraying basic aluminum chloride: spraying a basic aluminum chloride aqueous solution on the polyacrylonitrile fiber precursor II, followed by drying to prepare the polyacrylonitrile fiber precursor III;

[0018] Step S7, carbon powder spraying: dispersing carbon powder in the aqueous solution of perfluorolauryl alcohol polyoxyethylene ether in step S5 to prepare solution D, spraying solution D on polyacrylonitrile fiber precursor III, and then drying to prepare polyacrylonitrile fiber precursor IV;

[0019] Step S8, preparing a pre-oxidation gas atmosphere: replacing the gas in the pre-oxidation chamber with a mixed gas of oxygen and hydrogen bromide;

[0020] Step S9, radiation heating preoxidation: placing the polyacrylonitrile fiber precursor IV in the gas atmosphere of step S8, and preoxidizing by radiation heating to produce preoxidized fiber V;

[0021] Step S10, ultrasonic treatment: immersing the pre-oxidized fiber V in an aqueous solution of sodium β-anthraquinone sulfonate and using ultrasonic treatment to prepare the pre-oxidized fiber VI;

[0022] Step S11, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the pre-oxidized fiber VI in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the pre-oxidized fiber VII;

[0023] Step S12, carbonization treatment: placing the pre-oxidized fiber VII in nitrogen for heating and carbonization to prepare polyacrylonitrile-based carbon fiber.

[0024] As a preferred embodiment, the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:1 to 100:10.

[0025] As a preferred embodiment, the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.1:100 to 0.2:100.

[0026] As a preferred embodiment, the mass ratio of the polyoxyethylene sorbitan monopalmitate to the polyacrylonitrile-based copolymer is 0.2:100 to 0.4:100.

[0027] As a preferred solution, the fineness of the polyacrylonitrile fiber precursor I is 2D to 5D.

[0028] As a preferred solution, the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 1.5% to 2.5%; the immersion time is 1 hour to 2 hours; and the drying temperature is 110° C. to 130° C.

[0029] As a preferred solution, the mass concentration of the basic aluminum chloride aqueous solution is 1% to 2%; and the drying temperature is 110°C to 130°C.

[0030] As a preferred solution, the mass concentration of carbon powder in solution D is 5% to 15%, and the particle size of carbon powder is 6 microns to 10 microns; the drying temperature is 110° C. to 130° C.

[0031] As a preferred solution, the volume concentration of hydrogen bromide is 10% to 20%, and the volume concentration of oxygen is 80% to 90%.

[0032] As a preferred solution, the pre-oxidation temperature is 250° C. to 300° C., the time is 20 minutes to 60 minutes; the radiation frequency is 0.3 THz to 400 THz; and the traction is performed simultaneously, with a stretching length of 2% to 5%.

[0033] As a preferred solution, the ultrasonic frequency is 100KHz to 200KHz; the ultrasonic treatment time is 10 minutes to 30 minutes; and the mass concentration of the sodium β-anthraquinone sulfonate aqueous solution is 15% to 25%.

[0034] As a preferred solution, the carbonization temperature is 800° C. to 1200° C.; and the carbonization time is 1 hour to 2 hours.

[0035] A second aspect of the present invention provides a high temperature resistant polyacrylonitrile-based carbon fiber, wherein the high temperature resistant polyacrylonitrile-based carbon fiber is made by the aforementioned preparation method.

[0036] In a third aspect of the present invention, the high temperature resistant polyacrylonitrile-based carbon fiber is applied to fireproof fabrics.

[0037] In a fourth aspect of the present invention, the fireproof fabric is applied to fireproof clothing and fireproof equipment.

[0038] Through the above technical solutions, the present invention produces the following technical effects:

[0039] (1) By adding polyoxyethylene sorbitan monopalmitate, the void index of polyacrylonitrile fiber precursor is reduced and the quality of the precursor is improved.

[0040] (2) By adding 2-acrylamido-2-methylpropane sulfonic acid, the limiting oxygen index of pre-oxidized fiber is increased and the fire resistance is improved.

[0041] (3) The agglomeration rate of pre-oxidized fibers was reduced by impregnating with perfluorolauryl polyoxyethylene ether and spraying with carbon powder.

[0042] (4) By spraying basic aluminum chloride, the curl number of pre-oxidized fibers is increased and the softness is improved.

[0043] (5) Adding hydrogen bromide gas to oxygen can promote the pre-oxidation reaction and increase the oxidation rate. Within the same pre-oxidation time, the pre-oxidation degree is higher and the limiting oxygen index is higher.

[0044] (6) Use radiation heating to carry out pre-oxidation reaction to inhibit the formation of skin-core structure.

[0045] (7) Through ultrasonic action, tar-like impurities deposited on the surface of pre-oxidized fibers are removed to improve the quality of carbon fibers.

[0046] (8) The pre-oxidized fibers are treated with sodium β-anthraquinone sulfonate to remove the oxygen absorbed by the pre-oxidized fibers and improve the tensile strength of the carbon fibers. DETAILED DESCRIPTION

[0047] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and understandable, the applicant provides specific test examples and embodiments for explanation.

[0048] Denier is a measure of fiber size (linear density) used in the textile industry, defined as the fiber weight in grams per 9000 meters of fiber length and denoted by the letter D.

[0049] Test Example 1:

[0050] Purpose of the experiment: To investigate the effect of the accelerator 2-acrylamido-2-methylpropanesulfonic acid.

[0051] Preparation of test sample 1:

[0052] The polyacrylonitrile-based copolymer is dissolved in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 25%, and a spinning stock A is prepared; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:5;

[0053] A 45% dimethylacetamide aqueous solution is used as a coagulation bath, a spinning stock A is spun by wet spinning, and the slurry is pulled and stretched to prepare polyacrylonitrile fiber precursor; the polyacrylonitrile fiber precursor has a fineness of 3D;

[0054] The polyacrylonitrile fiber precursor was placed in an air atmosphere and heated for pre-oxidation to prepare pre-oxidized fiber, namely, test sample 1; the pre-oxidation temperature was 250° C. and the time was 60 minutes; and the fiber was simultaneously pulled and stretched to a length of 4%.

[0055] Preparation of test sample 2:

[0056] The polyacrylonitrile-based copolymer is dissolved in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 25%, and a spinning stock A is prepared; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:5;

[0057] Adding a promoter 2-acrylamido-2-methylpropane sulfonic acid to a spinning stock A to prepare a spinning stock B; the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.15:100;

[0058] A 45% dimethylacetamide aqueous solution is used as a coagulation bath, a spinning stock B is spun by a wet spinning method, and then pulled and stretched to prepare a polyacrylonitrile fiber precursor; the polyacrylonitrile fiber precursor has a fineness of 3D;

[0059] The polyacrylonitrile fiber precursor was placed in an air atmosphere and heated for pre-oxidation to prepare pre-oxidized fiber, namely, test sample 2; the pre-oxidation temperature was 250° C. and the time was 60 minutes; and the fiber was pulled at the same time and stretched to a length of 4%.

[0060] The limiting oxygen index of test sample 1 and test sample 2 was measured.

[0061] Limiting oxygen index detection method: Determine the limiting oxygen index in accordance with GB / T2406-2009.

[0062] Test results and conclusions: The test results are shown in the table below. The limiting oxygen index of the pre-oxidized fiber prepared after adding 2-acrylamido-2-methylpropane sulfonic acid is significantly higher than that without adding. The limiting oxygen index can reflect the degree of pre-oxidation reaction. A high limiting oxygen index indicates a high degree of pre-oxidation, and a low limiting oxygen index indicates an insufficient degree of pre-oxidation. After adding 2-acrylamido-2-methylpropane sulfonic acid, 2-acrylamido-2-methylpropane sulfonic acid acts as a pre-oxidation promoter, promotes the cyclization reaction, and increases the oxidation rate. Within the same pre-oxidation time, the pre-oxidation degree is higher and the limiting oxygen index is higher.

[0063] Table 1 Test Example 1 Test results:

[0064] Sample name Limiting oxygen index (%) Test sample 1 16 Test sample 2 41

[0065] Test Example 2:

[0066] Experimental purpose: To investigate the effect of polyoxyethylene sorbitan monopalmitate.

[0067] Preparation of test sample 3:

[0068] The polyacrylonitrile-based copolymer is dissolved in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 25%, and a spinning stock A is prepared; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:5;

[0069] Adding a promoter 2-acrylamido-2-methylpropane sulfonic acid to a spinning stock A to prepare a spinning stock B; the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.15:100;

[0070] The spinning stock B is spun by wet spinning with a dimethylacetamide aqueous solution having a mass concentration of 45% as a coagulation bath, and then drawn and stretched to prepare polyacrylonitrile fiber precursor, namely, test sample 3; the fineness of the polyacrylonitrile fiber precursor is 3D.

[0071] Preparation of test sample 4:

[0072] The polyacrylonitrile-based copolymer is dissolved in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 25%, and a spinning stock A is prepared; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:5;

[0073] Adding a promoter 2-acrylamido-2-methylpropane sulfonic acid to a spinning stock A to prepare a spinning stock B; the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.15:100;

[0074] Adding polyoxyethylene sorbitan monopalmitate to spinning stock B to prepare spinning stock C; the mass ratio of the polyoxyethylene sorbitan monopalmitate to the polyacrylonitrile-based copolymer is 0.3:100;

[0075] The spinning stock C was spun by wet spinning with a dimethylacetamide aqueous solution having a mass concentration of 45% as a coagulation bath, and then drawn and stretched to prepare polyacrylonitrile fiber precursor, namely, test sample 4; the fineness of the polyacrylonitrile fiber precursor was 3D.

[0076] The void index of test sample 3 and test sample 4 was measured.

[0077] Void index detection method: Take a 100g test sample with a length of 1 meter, weigh the sample, soak the test sample tow in 25℃ water for 10 hours, take it out and drain it for 1 hour, weigh the sample, calculate the weight increase, and take the ratio of the weight increase to the original weight as the void index. The void index reflects the voids in the polyacrylonitrile fiber strands.

[0078] Test results and conclusions: The test results are shown in the table below. The void index of the polyacrylonitrile fiber precursor prepared by adding polyoxyethylene sorbitan monopalmitate is significantly lower than that of the fiber without adding polyoxyethylene sorbitan monopalmitate.

[0079] During spinning, during the rapid solidification process of the polymer, the surface of the filament solidifies first, and the inner core solidifies at a slower rate, resulting in a "skin-core" effect. The "skin-core" effect reduces the diffusion rate of the coagulation bath into the fiber, and at the same time inhibits the coagulation bath from escaping from the fiber, resulting in pores in the micron range, including uneven micropores and macropores, which affect the fiber quality.

[0080] In the molecular structure of polyoxyethylene sorbitan monopalmitate, sorbitan is a hydrophilic group, while the palmitate part gives it lipophilic properties. This structure allows polyoxyethylene sorbitan monopalmitate to be dispersed in the oil phase and dissolved in the water phase.

[0081] During the coagulation process, the semi-solidified fiber is in an amorphous state. The present invention utilizes the hydrophilic and lipophilic properties of polyoxyethylene sorbitan monopalmitate to affect the diffusion rate of water and solvent into and out of the semi-solidified fiber, thereby reducing the coagulation speed difference between the fiber surface and the inner core, reducing the "skin-core" effect, and obtaining a low-void and more uniform structure in the newly solidified fiber.

[0082] Table 2 Test results of test example 2:

[0083] Sample name Void index (%) Test sample 3 6 Test sample 4 1

[0084] Test Example 3:

[0085] Experimental purpose: To investigate the effect of perfluorolauryl polyoxyethylene ether.

[0086] Preparation of test sample 5:

[0087] The polyacrylonitrile fiber precursor (test sample 4) was placed in an air atmosphere and heated for pre-oxidation to prepare pre-oxidized fiber, namely test sample 5; the pre-oxidation temperature was 250°C and the time was 60 minutes; at the same time, it was pulled and stretched to a length of 4%.

[0088] Preparation of test sample 6:

[0089] The polyacrylonitrile fiber precursor (test sample 4) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution and then dried to prepare a polyacrylonitrile fiber precursor (2); the mass concentration of the lauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0090] The polyacrylonitrile fiber precursor (2) is placed in an air atmosphere and heated for pre-oxidation to prepare a pre-oxidized fiber, namely the test sample 6; the pre-oxidation temperature is 250° C. and the time is 60 minutes; at the same time, it is pulled and stretched to a length of 4%.

[0091] The fiber aggregation rates of test samples 5 and 6 were measured.

[0092] Fiber agglomeration rate measurement method: cut the pre-oxidized fiber bundle into 3 mm lengths, put it into acetone and perform ultrasonic cleaning to remove the surfactant, and count the number of agglomerated filaments under a microscope, and calculate the ratio of the number of agglomerated filaments to the total number of filaments, which is the agglomeration rate.

[0093] Test results and conclusions: The test results are shown in the table below. The agglomeration rate of pre-oxidized fibers prepared after being impregnated with perfluorolauryl polyoxyethylene ether is significantly lower than that of the unimpregnated fibers.

[0094] When preoxidation is performed at high temperature, heat is locally accumulated in the fiber and causes the preoxidized fibers to agglomerate with each other, reducing the fiber quality.

[0095] Fluorine is an element with strong electronegativity, high oxidation potential and high ionization energy. On the one hand, this characteristic causes the fluorine-carbon bond (F-C) to have high bond energy, so the fluorocarbon chain structure is much more stable than the hydrocarbon structure and can withstand extreme high temperature environments. On the other hand, fluorine atoms are difficult to polarize, making the fluorocarbon chain less polar than the hydrocarbon chain. It is precisely because of this low polarity that the hydrophobic effect of the fluorocarbon chain is much stronger than that of the hydrocarbon chain, which also leads to weak mutual interaction between the fluorocarbon chains. The combined effect of these two factors makes the fluorocarbon surfactant molecules in the aqueous solution more inclined to leave the aqueous solution than other surfactant molecules, and orientedly aggregate and arrange into molecular membranes at the liquid / solid interface, forming a layer of fluorocarbon compounds on the fiber surface, thereby preventing fiber aggregation.

[0096] Table 3 Test results of test example 3:

[0097] Sample name Agglomeration rate (%) Test sample 5 6 Test sample 6 2

[0098] Test example 4:

[0099] Purpose of the experiment: To investigate the effect of basic aluminum chloride.

[0100] Preparation of test sample 7:

[0101] The polyacrylonitrile fiber precursor (test sample 4) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution and then dried to prepare a polyacrylonitrile fiber precursor (2); the mass concentration of the lauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0102] The basic aluminum chloride aqueous solution is sprayed onto the polyacrylonitrile fiber precursor (2), followed by drying to prepare the polyacrylonitrile fiber precursor (3); the basic aluminum chloride aqueous solution has a mass concentration of 1.5%; and the drying temperature is 120° C.;

[0103] The polyacrylonitrile fiber precursor (3) is placed in an air atmosphere and heated for pre-oxidation to prepare a pre-oxidized fiber, namely the test sample 7; the pre-oxidation temperature is 250° C. and the time is 60 minutes; at the same time, the fiber is pulled and stretched to a length of 4%.

[0104] The fiber crimp numbers of test samples 6 and 7 were measured.

[0105] Fiber crimp number determination method: at a speed of 100m / h, 1kg / cm 2 Filling pressure and 2kg / cm 2 Under the clamping pressure of , test sample 6 and test sample 7 are respectively made to curl, and the maximum curl number they can withstand is determined according to GB / T 14338-2008 Test method for curl performance of chemical fiber staple fibers. The curl number is the number of bends per unit length of chemical fiber. From one curl peak to an adjacent curl peak of the fiber is a curl. The larger the maximum curl number, the higher the fiber flexibility and the stronger the spinnability.

[0106] Test results and conclusions: The test results are shown in the table below. The number of crimps of pre-oxidized fibers prepared after spraying with basic aluminum chloride is significantly higher than that of unsprayed fibers.

[0107] When pre-oxidized at high temperature, the fiber becomes brittle and its flexibility is reduced. When the fiber is processed into yarn, it is easy to break and its spinnability is reduced.

[0108] The basic aluminum chloride used in the present invention contains hydroxyl groups and is water-soluble. It can not only be uniformly deposited on acrylonitrile fibers, but also effectively absorb and diffuse the heat generated during fiber oxidation, reduce excessive heat accumulation or temperature rise inside the fibers, thereby producing uniformly oxidized fibers with good curling properties.

[0109] Table 4 Test results of test example 4:

[0110] Sample name Curl number Test sample 6 3 Test sample 7 9

[0111] Test Example 5:

[0112] Purpose of the test: To investigate the effect of carbon powder spraying.

[0113] Preparation of test sample 8:

[0114] The polyacrylonitrile fiber precursor (test sample 4) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution and then dried to prepare a polyacrylonitrile fiber precursor (2); the mass concentration of the lauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0115] The basic aluminum chloride aqueous solution is sprayed onto the polyacrylonitrile fiber precursor (2), followed by drying to prepare the polyacrylonitrile fiber precursor (3); the basic aluminum chloride aqueous solution has a mass concentration of 1.5%; and the drying temperature is 120° C.;

[0116] Dispersing carbon powder in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution to prepare a carbon powder dispersion, spraying the carbon powder dispersion onto a polyacrylonitrile fiber precursor (3), and then drying to prepare a polyacrylonitrile fiber precursor (4); the mass concentration of the carbon powder in the carbon powder dispersion is 10%, and the carbon powder particle size is 8 microns; the drying temperature is 120°C;

[0117] The polyacrylonitrile fiber precursor (4) is placed in an air atmosphere and heated for pre-oxidation to prepare a pre-oxidized fiber (5), namely the test sample 8; the pre-oxidation temperature is 250° C. and the time is 60 minutes; at the same time, it is pulled and stretched to a length of 4%.

[0118] The fiber aggregation rates of test samples 7 and 8 were measured.

[0119] The fiber aggregation rate measurement method is consistent with that of Test Example 3.

[0120] Test results and conclusions: The test results are shown in the table below. The agglomeration rate of pre-oxidized fibers prepared after spraying with carbon powder is significantly lower than that of unsprayed fibers.

[0121] When pre-oxidation is carried out at high temperature, heat accumulates locally in the fiber, causing an uneven reaction, resulting in the production of tar-like substances on the fiber surface, which affects the physical properties of the fiber and also causes adhesion and agglomeration. After spraying carbon powder, the tar-like substances will be effectively adsorbed by the carbon powder, thereby reducing the fiber agglomeration rate.

[0122] Table 5 Test results of test example 5:

[0123] Sample name Agglomeration rate (%) Test sample 7 1.5 Test sample 8 No aggregation was observed

[0124] Test Example 6:

[0125] Experimental purpose: To investigate the effect of hydrogen bromide gas.

[0126] Preparation of test sample 9:

[0127] The polyacrylonitrile fiber precursor (test sample 4) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution and then dried to prepare a polyacrylonitrile fiber precursor (2); the mass concentration of the lauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0128] The basic aluminum chloride aqueous solution is sprayed onto the polyacrylonitrile fiber precursor (2), followed by drying to prepare the polyacrylonitrile fiber precursor (3); the basic aluminum chloride aqueous solution has a mass concentration of 1.5%; and the drying temperature is 120° C.;

[0129] Dispersing carbon powder in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution to prepare a carbon powder dispersion, spraying the carbon powder dispersion onto a polyacrylonitrile fiber precursor (3), and then drying to prepare a polyacrylonitrile fiber precursor (4); the mass concentration of the carbon powder in the carbon powder dispersion is 10%, and the carbon powder particle size is 8 microns; the drying temperature is 120°C;

[0130] The polyacrylonitrile fiber precursor (4) is placed in a mixed gas atmosphere of oxygen and hydrogen bromide, heated and pre-oxidized to produce a pre-oxidized fiber (5), namely the test sample 9; the pre-oxidation temperature is 250°C and the time is 60 minutes; at the same time, it is pulled and stretched to a length of 4%; the volume concentration of hydrogen bromide in the mixed gas is 15%, and the volume concentration of oxygen is 85%.

[0131] The limiting oxygen index of test sample 8 and test sample 9 was measured.

[0132] Limiting oxygen index detection method: Determine the limiting oxygen index in accordance with GB / T2406-2009.

[0133] Test results and conclusions: The test results are shown in the table below. The limiting oxygen index of the pre-oxidized fiber prepared in a mixed gas atmosphere of oxygen and hydrogen bromide is significantly higher than that of air. The limiting oxygen index can reflect the degree of pre-oxidation. A high limiting oxygen index indicates a high degree of pre-oxidation, and a low limiting oxygen index indicates an insufficient degree of pre-oxidation. After adding hydrogen bromide gas to oxygen, the pre-oxidation reaction can be promoted and the oxidation rate can be increased. Within the same pre-oxidation time, the pre-oxidation degree is higher and the limiting oxygen index is higher; when the same limiting oxygen index is reached, the pre-oxidation time is shorter.

[0134] Table 6 Test results of test example 6:

[0135] Sample name Limiting oxygen index (%) Test sample 8 45 Test sample 9 61

[0136] Test Example 7:

[0137] Experimental purpose: To investigate the effect of radiation heating in pre-oxidation.

[0138] Preparation of test sample 10:

[0139] The polyacrylonitrile fiber precursor (test sample 4) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution and then dried to prepare a polyacrylonitrile fiber precursor (2); the mass concentration of the lauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0140] The basic aluminum chloride aqueous solution is sprayed onto the polyacrylonitrile fiber precursor (2), followed by drying to prepare the polyacrylonitrile fiber precursor (3); the basic aluminum chloride aqueous solution has a mass concentration of 1.5%; and the drying temperature is 120° C.;

[0141] Dispersing carbon powder in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution to prepare a carbon powder dispersion, spraying the carbon powder dispersion onto a polyacrylonitrile fiber precursor (3), and then drying to prepare a polyacrylonitrile fiber precursor (4); the mass concentration of the carbon powder in the carbon powder dispersion is 10%, and the carbon powder particle size is 8 microns; the drying temperature is 120°C;

[0142] placing the polyacrylonitrile fiber precursor (4) in a mixed gas atmosphere of oxygen and hydrogen bromide, wherein the volume concentration of hydrogen bromide in the mixed gas is 15% and the volume concentration of oxygen is 85%;

[0143] Pre-oxidation is performed by means of radiation heating to produce pre-oxidized fibers (5), namely test sample 10; the pre-oxidation temperature is 250° C. and the time is 60 minutes; the radiation frequency is 200 THz; and the fibers are pulled at the same time and stretched to a length of 4%.

[0144] The skin-to-core ratios of test samples 9 and 10 were measured.

[0145] The skin-core ratio was determined by optical microscopy: the test samples were embedded in a mixture of epoxy resin and curing agent at a ratio of 15:2 (mass ratio) and cured at 60°C for 2 hours. The samples were sliced ​​using an EM TRIM2 ultrathin slicer from Leica, Germany. The sample thickness was about 400 nm. The slices were then observed using a 20X objective lens under a BX53M high-power optical microscope from Olympus, Japan. The optical density values ​​were analyzed using ImageJ software based on the different light transmittances of the cortex and core, and the skin-core ratio was calculated using the formula: cortex area of ​​the fiber cross section / total area*100%.

[0146] Test results and conclusions: The test results are shown in the table below. After the pre-oxidation reaction was carried out by radiation heating, the skin-core structure disappeared, and the radiation heating method effectively inhibited the formation of the skin-core structure.

[0147] Traditional pre-oxidation reaction heating mostly uses equipment such as ovens. Heat and oxygen diffuse from the fiber surface to the inner core. Heat and oxygen are both promoting factors of the pre-oxidation reaction, which leads to excessive pre-oxidation of the fiber surface, forming a dense trapezoidal structure, which in turn hinders the diffusion of oxygen into the interior of the fiber, resulting in a low degree of pre-oxidation reaction in the fiber core, forming a skin-core structure.

[0148] The heat transfer method of radiation heating is different from that of traditional oven heating. Radiant heating has strong penetrating power, which generates heat inside and on the surface of the fiber at the same time, and the pre-oxidation reaction is carried out at the same time. After the pre-oxidation reaction releases heat, the heat diffuses from the fiber core to the surface, resulting in a high temperature in the core and a low temperature in the surface, which accelerates the cyclization reaction of the core, thereby reducing the difference in pre-oxidation reaction between the core and the surface, preventing the formation of a skin-core structure, improving fiber uniformity, and improving fiber quality.

[0149] By controlling the frequency of the radiation wave and making it consistent with the absorption wave of the polyacrylonitrile fiber precursor, the two can achieve resonance, so that the temperature of the fiber surface and the inner core can be kept consistent at the initial stage of heating, avoiding the temperature difference effect of traditional heating.

[0150] In addition, radiation heating has the advantages of convenient and accurate temperature control and high thermal efficiency.

[0151] Table 7 Test results of test example 7:

[0152] Sample name Skin-to-core ratio (%) Test sample 9 89.1 Test sample 10 99.9

[0153] Test Example 8:

[0154] Experimental purpose: To investigate the effect of ultrasonic treatment.

[0155] Preparation of test sample 11:

[0156] The test sample 10 is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution and then dried to prepare a pre-oxidized fiber (7); the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 2%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0157] The pre-oxidized fiber (7) is placed in nitrogen and heated for carbonization to prepare polyacrylonitrile-based carbon fiber, namely the test sample 11; the carbonization temperature is 1000° C.; and the carbonization time is 1.5 hours.

[0158] Preparation of test sample 12:

[0159] The test sample 10 is immersed in an aqueous solution and treated with ultrasound to prepare a pre-oxidized fiber (6); the ultrasound frequency is 1500 KHz; and the ultrasound treatment time is 20 minutes;

[0160] The pre-oxidized fiber (6) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then dried to prepare a pre-oxidized fiber (7); the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 2%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0161] The pre-oxidized fiber (7) is placed in nitrogen and heated for carbonization to prepare polyacrylonitrile-based carbon fiber, namely the test sample 12; the carbonization temperature is 1000° C.; and the carbonization time is 1.5 hours.

[0162] The tensile strength of the test samples 11 and 12 was measured. The method for measuring the tensile strength is prior art and will not be described in detail here.

[0163] Test results and conclusions: The test results are shown in the table below. After the pre-oxidized fiber is treated with ultrasonic waves and carbonized, the tensile strength of the carbon fiber increases significantly.

[0164] Through the action of ultrasound, the carbon powder-tar deposited on the surface of the pre-oxidized fiber can be removed. When the pre-oxidized fiber is carbonized, high-quality carbon fiber is obtained.

[0165] Table 8 Test results of test example 8:

[0166] Sample name Tensile Strength (ksi) Test sample 11 268 Test sample 12 353

[0167] Test Example 9:

[0168] Experimental purpose: To investigate the effect of sodium β-anthraquinone sulfonate.

[0169] Preparation of test sample 13:

[0170] The test sample 10 is immersed in an aqueous solution of sodium β-anthraquinone sulfonate and treated with ultrasound to prepare a pre-oxidized fiber (6); the ultrasound frequency is 1500 KHz; the ultrasound treatment time is 20 minutes; the mass concentration of the aqueous solution of sodium β-anthraquinone sulfonate is 20%;

[0171] The pre-oxidized fiber (6) is immersed in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then dried to prepare a pre-oxidized fiber (7); the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 2%; the immersion time is 1.5 hours; and the drying temperature is 120°C;

[0172] The pre-oxidized fiber (7) is placed in nitrogen and heated for carbonization to prepare polyacrylonitrile-based carbon fiber, namely test sample 13; the carbonization temperature is 1000° C.; and the carbonization time is 1.5 hours.

[0173] The tensile strength of the test samples 12 and 13 was measured. The method for measuring the tensile strength is prior art and will not be described in detail here.

[0174] Test results and conclusions: The test results are shown in the table below. After being treated with sodium β-anthraquinone sulfonate, the tensile strength of the pre-oxidized fiber increased significantly after carbonization reaction.

[0175] Pre-oxidized fibers are carbonized in an oxygen-free, high-temperature environment to obtain carbon fibers. Oxygen during carbonization will reduce the quality of carbon fibers. However, pre-oxidized fibers are prepared in an oxygen-containing environment and inevitably contain a small amount of oxygen, which affects the quality of carbon fibers.

[0176] The present invention uses sodium β-anthraquinone sulfonate reducing solution to treat pre-oxidized fibers to remove oxygen absorbed by the pre-oxidized fibers, and then treats the fibers at high temperature in a non-oxidizing atmosphere, thereby eliminating the influence of oxygen oxidation on the carbonization reaction, significantly improving the tensile strength of the carbon fibers, and further improving the limiting oxygen index.

[0177] Table 9 Test Example 9 Test results:

[0178] Sample name Tensile Strength (ksi) Limiting oxygen index (%) Test sample 12 353 63 Test sample 13 466 75

[0179] Embodiment 1:

[0180] The high temperature resistant polyacrylonitrile-based carbon fiber was prepared according to the following method:

[0181] Step S1, preparing spinning stock A: dissolving a polyacrylonitrile-based copolymer in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 20%, thereby preparing spinning stock A; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:1;

[0182] Step S2, adding an accelerator: adding an accelerator 2-acrylamido-2-methylpropane sulfonic acid to a spinning stock A to prepare a spinning stock B; the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.1:100;

[0183] Step S3, adding polyoxyethylene sorbitan monopalmitate: adding polyoxyethylene sorbitan monopalmitate to spinning stock B to prepare spinning stock C; the mass ratio of the polyoxyethylene sorbitan monopalmitate to the polyacrylonitrile-based copolymer is 0.2:100;

[0184] Step S4, preparing polyacrylonitrile fiber precursor: using a dimethylacetamide aqueous solution with a mass concentration of 40% as a coagulation bath, spinning the spinning stock C by wet spinning, pulling and stretching, to prepare polyacrylonitrile fiber precursor I; the polyacrylonitrile fiber precursor I has a fineness of 2D;

[0185] Step S5, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the polyacrylonitrile fiber precursor I in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the polyacrylonitrile fiber precursor II; the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 1.5%; the immersion time is 1 hour; the drying temperature is 110° C.;

[0186] Step S6, spraying basic aluminum chloride: spraying a basic aluminum chloride aqueous solution on the polyacrylonitrile fiber precursor II, followed by drying to produce the polyacrylonitrile fiber precursor III; the basic aluminum chloride aqueous solution has a mass concentration of 1%; the drying temperature is 110° C.;

[0187] Step S7, carbon powder spraying: dispersing carbon powder in the aqueous solution of perfluorolauryl polyoxyethylene ether in step S5 to prepare solution D, spraying solution D on polyacrylonitrile fiber precursor III, and then drying to prepare polyacrylonitrile fiber precursor IV; the mass concentration of carbon powder in solution D is 5%, and the particle size of carbon powder is 6 microns; the drying temperature is 110° C.;

[0188] Step S8, preparing a pre-oxidation gas atmosphere: replacing the gas in the pre-oxidation chamber with a mixed gas of oxygen and hydrogen bromide, wherein the volume concentration of hydrogen bromide is 10% and the volume concentration of oxygen is 90%;

[0189] Step S9, radiation heating preoxidation: placing the polyacrylonitrile fiber precursor IV in the gas atmosphere of step S8, preoxidizing by radiation heating to prepare preoxidized fiber V; the preoxidation temperature is 250°C, the time is 20 minutes; the radiation frequency is 0.3 THz; and pulling at the same time, the stretching length is 2%;

[0190] Step S10, ultrasonic treatment: immersing the pre-oxidized fiber V in an aqueous solution of sodium β-anthraquinone sulfonate and using ultrasonic treatment to prepare pre-oxidized fiber VI; the ultrasonic frequency is 100 KHz; the ultrasonic treatment time is 10 minutes; the mass concentration of the aqueous solution of sodium β-anthraquinone sulfonate is 15%;

[0191] Step S11, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the pre-oxidized fiber VI in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, followed by drying to prepare a pre-oxidized fiber VII; the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 1.5%; the immersion time is 1 hour; the drying temperature is 110° C.;

[0192] Step S12, carbonization treatment: placing the pre-oxidized fiber VII in nitrogen for heating and carbonization to prepare polyacrylonitrile-based carbon fiber; the carbonization temperature is 800° C.; the carbonization time is 1 hour.

[0193] Embodiment 2:

[0194] The high temperature resistant polyacrylonitrile-based carbon fiber was prepared according to the following method:

[0195] Step S1, preparing spinning stock A: dissolving a polyacrylonitrile-based copolymer in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 25%, thereby preparing spinning stock A; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:5;

[0196] Step S2, adding an accelerator: adding an accelerator 2-acrylamido-2-methylpropane sulfonic acid to the spinning stock A to prepare the spinning stock B; the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.15:100;

[0197] Step S3, adding polyoxyethylene sorbitan monopalmitate: adding polyoxyethylene sorbitan monopalmitate to spinning stock B to prepare spinning stock C; the mass ratio of the polyoxyethylene sorbitan monopalmitate to the polyacrylonitrile-based copolymer is 0.3:100;

[0198] Step S4, preparing polyacrylonitrile fiber precursor: using a 45% mass concentration of dimethylacetamide aqueous solution as a coagulation bath, spinning the spinning pulp C by wet spinning, pulling and stretching, to prepare polyacrylonitrile fiber precursor I; the polyacrylonitrile fiber precursor I has a fineness of 3D;

[0199] Step S5, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the polyacrylonitrile fiber precursor I in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the polyacrylonitrile fiber precursor II; the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; the drying temperature is 120° C.;

[0200] Step S6, spraying basic aluminum chloride: spraying a basic aluminum chloride aqueous solution on the polyacrylonitrile fiber precursor II, followed by drying to produce the polyacrylonitrile fiber precursor III; the basic aluminum chloride aqueous solution has a mass concentration of 1.5%; and the drying temperature is 120° C.;

[0201] Step S7, carbon powder spraying: dispersing carbon powder in the perfluorolauryl alcohol polyoxyethylene ether aqueous solution of step S5 to prepare solution D, spraying solution D on polyacrylonitrile fiber precursor III, and then drying to prepare polyacrylonitrile fiber precursor IV; the mass concentration of carbon powder in solution D is 10%, and the particle size of carbon powder is 8 microns; the drying temperature is 120°C;

[0202] Step S8, preparing a pre-oxidation gas atmosphere: replacing the gas in the pre-oxidation chamber with a mixed gas of oxygen and hydrogen bromide, wherein the volume concentration of hydrogen bromide is 15% and the volume concentration of oxygen is 85%;

[0203] Step S9, radiation heating preoxidation: placing the polyacrylonitrile fiber precursor IV in the gas atmosphere of step S8, preoxidizing by radiation heating to prepare preoxidized fiber V; the preoxidation temperature is 270°C, the time is 40 minutes; the radiation frequency is 200 THz; and pulling at the same time, the stretching length is 3%;

[0204] Step S10, ultrasonic treatment: immersing the pre-oxidized fiber V in an aqueous solution of sodium β-anthraquinone sulfonate and using ultrasonic treatment to prepare pre-oxidized fiber VI; the ultrasonic frequency is 150 KHz; the ultrasonic treatment time is 20 minutes; the mass concentration of the aqueous solution of sodium β-anthraquinone sulfonate is 20%;

[0205] Step S11, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the pre-oxidized fiber VI in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, followed by drying to prepare a pre-oxidized fiber VII; the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 2.0%; the immersion time is 1.5 hours; the drying temperature is 120° C.;

[0206] Step S12, carbonization treatment: placing the pre-oxidized fiber VII in nitrogen for heating and carbonization to prepare polyacrylonitrile-based carbon fiber; the carbonization temperature is 1000° C.; the carbonization time is 1.5 hours.

[0207] Embodiment 3:

[0208] The high temperature resistant polyacrylonitrile-based carbon fiber was prepared according to the following method:

[0209] Step S1, preparing spinning stock A: dissolving a polyacrylonitrile-based copolymer in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 30%, to prepare spinning stock A; the molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:10;

[0210] Step S2, adding an accelerator: adding an accelerator 2-acrylamido-2-methylpropane sulfonic acid to a spinning stock A to prepare a spinning stock B; the molar ratio of the 2-acrylamido-2-methylpropane sulfonic acid to the acrylonitrile monomer is 0.2:100;

[0211] Step S3, adding polyoxyethylene sorbitan monopalmitate: adding polyoxyethylene sorbitan monopalmitate to spinning stock B to prepare spinning stock C; the mass ratio of the polyoxyethylene sorbitan monopalmitate to the polyacrylonitrile-based copolymer is 0.4:100;

[0212] Step S4, preparing polyacrylonitrile fiber precursor: using a 50% dimethylacetamide aqueous solution as a coagulation bath, spinning the spinning stock C by wet spinning, pulling and stretching, to prepare polyacrylonitrile fiber precursor I; the polyacrylonitrile fiber precursor I has a fineness of 5D;

[0213] Step S5, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the polyacrylonitrile fiber precursor I in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the polyacrylonitrile fiber precursor II; the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 2.5%; the immersion time is 2 hours; the drying temperature is 130° C.;

[0214] Step S6, spraying basic aluminum chloride: spraying a basic aluminum chloride aqueous solution on the polyacrylonitrile fiber precursor II, followed by drying to produce the polyacrylonitrile fiber precursor III; the basic aluminum chloride aqueous solution has a mass concentration of 2%; and the drying temperature is 130° C.;

[0215] Step S7, carbon powder spraying: dispersing carbon powder in the aqueous solution of perfluorolauryl polyoxyethylene ether in step S5 to prepare solution D, spraying solution D on polyacrylonitrile fiber precursor III, and then drying to prepare polyacrylonitrile fiber precursor IV; the mass concentration of carbon powder in solution D is 15%, and the particle size of carbon powder is 10 microns; the drying temperature is 130° C.;

[0216] Step S8, preparing a pre-oxidation gas atmosphere: replacing the gas in the pre-oxidation chamber with a mixed gas of oxygen and hydrogen bromide, wherein the volume concentration of hydrogen bromide is 20% and the volume concentration of oxygen is 90%;

[0217] Step S9, radiation heating preoxidation: placing the polyacrylonitrile fiber precursor IV in the gas atmosphere of step S8, preoxidizing by radiation heating to prepare preoxidized fiber V; the preoxidation temperature is 300°C, the time is 60 minutes; the radiation frequency is 400 THz; and pulling at the same time, the stretching length is 5%;

[0218] Step S10, ultrasonic treatment: immersing the pre-oxidized fiber V in an aqueous solution of sodium β-anthraquinone sulfonate and using ultrasonic treatment to prepare pre-oxidized fiber VI; the ultrasonic frequency is 200 KHz; the ultrasonic treatment time is 30 minutes; the mass concentration of the aqueous solution of sodium β-anthraquinone sulfonate is 25%;

[0219] Step S11, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the pre-oxidized fiber VI in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, followed by drying to prepare a pre-oxidized fiber VII; the mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 12.5%; the immersion time is 2 hours; the drying temperature is 130° C.;

[0220] Step S12, carbonization treatment: placing the pre-oxidized fiber VII in nitrogen for heating and carbonization to prepare polyacrylonitrile-based carbon fiber; the carbonization temperature is 1200° C.; and the carbonization time is 2 hours.

[0221] The void index, curl number, aggregation rate, limiting oxygen index, and skin-core ratio of the pre-oxidized fibers V of Example 1, Example 2, and Example 3 were tested, and the results are shown in the table below.

[0222] The pre-oxidized fiber V prepared by the present invention has extremely low void index and agglomeration rate, and a relatively high skin-core ratio, which is beneficial to the quality control of the pre-oxidized fiber and to the subsequent quality improvement of the carbon fiber. The pre-oxidized fiber V prepared by the present invention has a high curl number and good flexibility, which can improve the spinnability in the production process and reduce the risk of fiber breakage. The pre-oxidized fiber V prepared by the present invention has a high limiting oxygen index, can withstand high temperatures, and has good flame retardancy.

[0223] Table 10 Example pre-oxidized fiber V test results:

[0224] Sample name Void index (%) Number of curls (pcs / cm) Agglomeration rate (%) Limiting oxygen index (%) Skin-to-core ratio (%) Example 1 1.0 9 No aggregation was observed 60 99.9 Example 2 1.0 9 No aggregation was observed 62 99.9 Example 3 0.9 10 No aggregation was observed 61 99.9

[0225] The aggregation rate, limiting oxygen index and tensile strength of the polyacrylonitrile-based carbon fibers of Example 1, Example 2 and Example 3 were tested, and the results are shown in the table below.

[0226] The polyacrylonitrile-based carbon fiber prepared by the invention has an extremely low aggregation rate, thereby improving the qualified rate of the carbon fiber; a high limiting oxygen index, high temperature resistance, and good flame retardancy; and a high tensile strength and high quality.

[0227] Table 11 Example polyacrylonitrile-based carbon fiber test results:

[0228] Sample name Agglomeration rate (%) Limiting oxygen index (%) Tensile Strength (ksi) Example 1 No aggregation was observed 73 465 Example 2 No aggregation was observed 75 470 Example 3 No aggregation was observed 75 471

Claims

1. A method for preparing high temperature resistant polyacrylonitrile-based carbon fiber, characterized in that: The following steps are involved: Step S1, preparing spinning stock A: dissolving a polyacrylonitrile-based copolymer in dimethylacetamide to make the mass concentration of the polyacrylonitrile-based copolymer reach 20% to 30%, to prepare a spinning stock A; Step S2, adding an accelerator: adding an accelerator 2-acrylamido-2-methylpropanesulfonic acid to the spinning stock A to prepare the spinning stock B; Step S3, adding polyoxyethylene sorbitan monopalmitate: adding polyoxyethylene sorbitan monopalmitate to spinning stock B to prepare spinning stock C; Step S4, preparing polyacrylonitrile fiber precursor: using a dimethylacetamide aqueous solution with a mass concentration of 40% to 50% as a coagulation bath, spinning the spinning stock C by wet spinning, pulling and stretching, and preparing polyacrylonitrile fiber precursor I; Step S5, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the polyacrylonitrile fiber precursor I in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the polyacrylonitrile fiber precursor II; Step S6, spraying basic aluminum chloride: spraying a basic aluminum chloride aqueous solution on the polyacrylonitrile fiber precursor II, followed by drying to prepare the polyacrylonitrile fiber precursor III; Step S7, carbon powder spraying: dispersing carbon powder in the aqueous solution of perfluorolauryl alcohol polyoxyethylene ether in step S5 to prepare solution D, spraying solution D on polyacrylonitrile fiber precursor III, and then drying to prepare polyacrylonitrile fiber precursor IV; Step S8, preparing a pre-oxidation gas atmosphere: replacing the gas in the pre-oxidation chamber with a mixed gas of oxygen and hydrogen bromide; Step S9, radiation heating preoxidation: placing the polyacrylonitrile fiber precursor IV in the gas atmosphere of step S8, and preoxidizing by radiation heating to produce preoxidized fiber V; Step S10, ultrasonic treatment: immersing the pre-oxidized fiber V in an aqueous solution of sodium β-anthraquinone sulfonate and using ultrasonic treatment to prepare the pre-oxidized fiber VI; Step S11, perfluorolauryl alcohol polyoxyethylene ether treatment: immersing the pre-oxidized fiber VI in a perfluorolauryl alcohol polyoxyethylene ether aqueous solution, and then drying to prepare the pre-oxidized fiber VII; Step S12, carbonization treatment: placing the pre-oxidized fiber VII in nitrogen for heating and carbonization to prepare polyacrylonitrile-based carbon fiber.

2. The preparation method according to claim 1, characterized in that: The molar ratio of acrylonitrile monomer to vinyl acetate in the polyacrylonitrile-based copolymer is 100:1 to 100:

10.

3. The preparation method according to claim 2, characterized in that: The molar ratio of the 2-acrylamido-2-methylpropanesulfonic acid to the acrylonitrile monomer is 0.1:100 to 0.2:

100.

4. The preparation method according to claim 3, characterized in that: The mass ratio of the polyoxyethylene sorbitan monopalmitate to the polyacrylonitrile-based copolymer is 0.2:100 to 0.4:

100.

5. The preparation method according to claim 4, characterized in that: The fineness of the polyacrylonitrile fiber precursor I is 2D-5D.

6. The preparation method according to claim 5, characterized in that: The mass concentration of the perfluorolauryl alcohol polyoxyethylene ether aqueous solution is 1.5% to 2.5%; the immersion time is 1 hour to 2 hours; and the drying temperature is 110° C. to 130° C.

7. The preparation method according to claim 6, characterized in that: The mass concentration of the basic aluminum chloride aqueous solution is 1% to 2%; the drying temperature is 110° C. to 130° C.

8. The preparation method according to claim 7, characterized in that: The mass concentration of the carbon powder in solution D is 5% to 15%, and the particle size of the carbon powder is 6 microns to 10 microns; the drying temperature is 110° C. to 130° C.

9. A high temperature resistant polyacrylonitrile-based carbon fiber, characterized in that: The high temperature resistant polyacrylonitrile-based carbon fiber is made by the preparation method described in claim 8.

10. Use of the high temperature resistant polyacrylonitrile-based carbon fiber according to claim 9 in fireproof fabrics.

Citation Information

Patent Citations

  • Porous nano carbon fiber material, lithium battery cathode material and cathode plate

    CN102127828A

  • Polyacrylonitrile-based carbon fiber precursor polymer and preparation method thereof, and polyacrylonitrile-based carbon fiber and preparation method thereof

    CN110305247A

  • Carbon nanofiber, preparation method thereof and application of carbon nanofiber in positive electrode material

    CN114477139A

  • Preparation method of modified polyacrylonitrile fiber

    CN116876116A

  • Composite nanofiber material as well as preparation method and application thereof

    CN117328166A

Cited By

  • Preparation method for high-temperature-resistant polyacrylonitrile-based carbon fibers and use thereof in fire-resistant fabrics

    WO2026171020A1